MUSTAQILLIK YILLARIDA MILLATLAR O‘RTASIDAGI MUNOSABATLAR: FALSAFIY TAHLIL (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
This article examines the formation, stages of development of interethnic relations and their philosophical analysis since the independence of Uzbekistan. The principles of interethnic harmony and tolerance are considered as one of the main directions of political, social and spiritual reforms carried out in the country. The article analyzes the role of philosophy in social integration, the moral foundations of interpersonal communication, and the impact of intercultural dialogue on national security and social stability. The rise of interethnic relations to a new level during the years of independence is explained as the philosophical basis of the idea of a “New Uzbekistan.”